Psychological bases for teaching elementary schoolchildren simple experimentation - Chudinova, E.V.; Shishkina, I.A. (Psihologičeskaâ nauka i obrazovanie, 2025)
Context and relevance. Experimentation as a general way of acting and thinking provides the basis for understanding all the natural sciences. That is why the ability to experiment is considered an important outcome of modern primary education. However, the conditions of effective training of junior schoolchildren in experimentation and the age possibilities of mastering this method of action have not been identified, which determines the relevance of this study. Objective. To describe the peculiarities of the simplest experimentation as a way of action and to characterise the age possibilities and conditions of mastering this way by junior schoolchildren through the design of experimental teaching. Hypothesis. Planning of the simplest experiments is included in the age possibilities of junior schoolchildren. The effectiveness of mastering the mode of action depends on the independence of pupils in discovering the need to control the conditions of the experiment. Methods and materials. Logical and logical-psychological analysis of the simplest experimentation. Formative experiment (analysis of video recordings). Comparative survey: an experimental class (27 pupils, 14 girls and 13 boys), which was taught experimentation in accordance with the principles of the D.B. Elkonin-V.V. Davydov system, and three control classes (two second classes, a total of 50 pupils, including 20 girls and 30 boys, and one fourth class, 25 pupils, including 10 girls and 15 boys), taught according to the traditional method. Results. Second grade students who were taught experimentation through setting and solving a learning problem demonstrated an understanding of the differences between experimental and control conditions and planned experiments at the level of fourth graders taught using the traditional curriculum (Mann-Whitney U-criterion, p = 0,117). Analysis of lesson videos and control measurements revealed dynamics and a key difficulty in mastering experimentation related to the need to simultaneously perform two opposite actions - opposing and equalising conditions for experimental and control subjects. Conclusions. It is shown that the simplest experimentation is accessible for mastering by junior schoolchildren, but the essential condition of mastering is the pupils' independent discovery of the necessity of controlling the conditions of experience. It is recommended to strengthen the activity character of teaching experimentation in traditional primary schools in order to achieve this important meta-subject result. Контекст и актуальность. Экспериментирование как общий способ действия и мышления создает базу для понимания всех естественных наук. Поэтому умение экспериментировать считается важным результатом современного начального образования. Однако условия эффективного обучения младших школьников экспериментированию и возрастные возможности усвоения этого способа действий не выявлены, что определяет актуальность данного исследования. Цель. Установить особенности простейшего экспериментирования как способа действия и охарактеризовать возрастные возможности и условия освоения этого способа младшими школьниками через проектирование экспериментального обучения. Гипотеза. Планирование простейших экспериментов входит в возрастные возможности младших школьников. Эффективность освоения способа действий зависит от самостоятельности учеников в открытии необходимости контроля условий эксперимента. Методы и материалы. Логико-предметный и логико-психологический анализ простейшего экспериментирования. Анализ видеозаписей формирующего эксперимента. Сравнительное обследование: экспериментальный класс (27 учеников, 14 девочек и 13 мальчиков), который обучался экспериментированию в соответствии с принципами системы Д.Б. Эльконина-В.В. Давыдова, и три контрольных класса (два вторых класса, всего 50 учеников, из них 20 девочек и 30 мальчиков, один четвертый класс, 25 учеников, из них 10 девочек и 15 мальчиков), обучавшиеся по традиционной методике. Результаты. Ученики второго класса, обучавшиеся экспериментированию через постановку и решение учебной задачи, продемонстрировали понимание различий между экспериментальными и контрольными условиями и планировали эксперименты на уровне четвероклассников, обучающихся по традиционной программе (U-критерий Манна-Уитни, p = 0,117). Анализ видеозаписей уроков и контрольные замеры выявили динамику и ключевую трудность в освоении экспериментирования, связанную с необходимостью одновременного выполнения двух противоположных действий - противопоставления и уравнивания условий для экспериментальных и контрольных объектов. Выводы. Показано, что простейшее экспериментирование доступно для освоения младшими школьниками, однако существенным условием освоения является самостоятельное открытие учениками необходимости контроля условий опыта. Рекомендовано для достижения этого важнейшего метапредметного результата усилить деятельностный характер обучения экспериментированию в традиционной начальной школе.